Impact of interleukin‐6 on T cells in kidney transplant recipients. (1st December 2022) - Chandran, Sindhu; Tang, Qizhi
Abstract : Interleukin‐6 (IL‐6), a multifunctional proinflammatory cytokine, plays a key role in T cell activation, survival, and differentiation. Acting as a switch that induces the differentiation of naïve T cells into Th17 cells and inhibits their development into regulatory T cells, IL‐6 promotes rejection and abrogates tolerance. Therapies that target IL‐6 signaling include antibodies to IL‐6 and the IL‐6 receptor and inhibitors of janus kinases; several of these therapeutics have demonstrated robust clinical efficacy in autoimmune and inflammatory diseases. Clinical trials of IL‐6 inhibition in kidney transplantation have focused primarily on its effects on B cells, plasma cells, and HLA antibodies. In this review, we summarize the impact of IL‐6 on T cells in experimental models of transplant and describe the effects of IL‐6 inhibition on the T cell compartment in kidney transplant recipients.